Peran Kolektivisme dan Agreeableness terhadap Perilaku Altruisme Prajurit TNI AD - Fajratul Izzah, Misyka; Fitriani, Annisa; Isnaini, Nurul (LP3M, Universitas Muhammadiyah Kendari, 2025)
This study aims to analyze how the interaction between collectivism culture and agreeableness personality contributes in shaping altruistic behavior in army soldiers. This study uses a quantitative approach. The subjects of this study were soldiers of the Army who served in the Infantry Battalion 143 / Tri Wira Eka Jaya or Yonif 143 / TWEJ. Samples were collected using purposive sampling technique. Data analysis was performed using multiple regression analysis techniques. The results showed that the culture of collectivism plays a significant role in increasing altruistic behavior, where individuals who have a collective orientation tend to adapt more easily to social norms that support altruistic actions. In addition, agreeableness personality also contributes to increasing altruistic behavior, especially in the context of teamwork and concern for unit colleagues. These findings confirm the importance of cultural and personality factors in shaping prosocial behavior in the military environment, as well as their implications in TNI AD personnel development strategies to increase cooperation and solidarity.